(3QaY GdMLH GdeSJhQI Yf eMGSf GdebUhQIs - (3CHhGdbGSe eMeO Hf CMeO Hf eMeO GdMSjfj GdSHJi GdeYQha HGdTQja GdZQfGWis; (3MGRe GdbQWGLfj , MGRe Hf eMeO Hf MSf Hf MGRe, CHh GdMSf,J (B684 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG JCedJ ebUhQI GdGeGe GdChMO CHj GdMSf CdajJgG JLeY VQhHG ef GdGMSGS hJTJed Ydi CaGfjf ef GdHjGf s
(3BNQgG (B:s
(3hGJjJ HeG jMUd efg GdbGQF Ydi QTGO abO hajJ HeG hYOJ s
(3HChdgG JQLeI dUGMH GdebUhQI efbhdI ef GdSjhWi hGdebQis
(3ai GdCYdGe(B: (3GdefThQIs
(3HOd GdeSJhQI hbO CKHJfG eG ai GdeNWhW hEjVGM Gdecfhf hGdeWHhYs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs